Pulsed Nd:YAG laser deposition of indium tin oxide thin films in different gases and organic light emitting device applications - YONG, T; TOU, T; YOW, H; SAFRAN, G (ELSEVIER SCIENCE SA, 2008)
The microstructures, electrical and optical properties of indium-doped tin oxide (ITO) films, deposited on glass substrates in different background gases by a pulsed Nd:YAG laser, were characterized. The optimal pressure for obtaining the lowest resistivity in ITO thin film is inversely proportional to the molecular weight of the background gases, namely the argon (Ar), oxygen (02), nitrogen (N-2) and helium (He). While substrate heating to 250 degrees C decreased the ITO resistivity to < 4 x 10(-4) Omega cm, obtaining the optical transmittance of higher than 90% depended mainly on the background gas pressure for O-2 and Ar. Obtaining the lowest ITO resistivity, however, did not beget a high optical transmittance for ITO deposition in N-2 and He. Scanning electron microscope pictures show distinct differences in microstructures due to the background gas: nanostructures when using Ar and N-2 but polycrystalline for using O-2 and He. The ITO surface roughness varied with the deposition distance. The effects on the molecularly doped, single-layer organic light emitting device (OLED) operation and performance were also investigated. Only ITO thin films prepared in O-2 and Ar are suitable for the fabrication OLED with performance comparable to that fabricated on the commercially available, magnetron-sputtered ITO. (c) 2008 Elsevier B.V. All rights reserved.